2017
DOI: 10.24198/jkp.v5i1.348
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Caregiver dan Kekambuhan Klien Skizofrenia

Abstract: Caregiver merupakan orang yang bertanggung jawab memberikan perawatan secara langsung dalam segala situasi,baik saat pasien kambuh atau tidak kambuh. Beberapa faktor caregiver yang berhubungan dengan kekambuhanpasien skizofrenia adalah dukungan keluarga, pengetahuan tentang pengobatan skizofrenia, peristiwa kehidupan yang penuh stres, dan kualitas hidup caregiver. Penelitian ini bertujuan untuk menganalisis faktor caregiver yang berhubungan dengan kekambuhan pasien skizofrenia. Penelitian ini merupakan penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…Family income is one manifestation of intrumental support that will be used in seeking mental health services in caring for family members of mental disorders (Friedman, 2010). This is in line with the results of research conducted by Farkhah (2017). This indicates that one of the factors that affect the healing of the patients is the family's economic condition.…”
Section: Bsupporting
confidence: 89%
“…Family income is one manifestation of intrumental support that will be used in seeking mental health services in caring for family members of mental disorders (Friedman, 2010). This is in line with the results of research conducted by Farkhah (2017). This indicates that one of the factors that affect the healing of the patients is the family's economic condition.…”
Section: Bsupporting
confidence: 89%
“…Family is the smallest unit of the community and members have respective roles including providing health care and giving care for the sick family member [7]. Family is a resource that is directly responsible for giving continuous care and preventing relapse of schizophrenia patients at home [8]. Most of the caregivers in this study are parents and male.…”
Section: Discussionmentioning
confidence: 99%
“…Farkah (2017) stated that giving good treatment will increase hope and a sense of optimism which will certainly improve the patient's recovery, while bad and insulting words will certainly worsen health. The role of the family as a caregiver will be a very important role in the health of patients (13). The study by Komalah (2016) showed that there was a significant reduction in families anxiety in caring for diabetes mellitus ulcer patients after being given family psychoeducation with a p value of 0.000 <α (0.05) (14).…”
Section: Discussionmentioning
confidence: 99%